P111: Presentations for hypoglycemia associated with diabetes mellitus to emergency departments in a Canadian province: a database and epidemiological analysis. (2nd June 2016) - Alexiu, C.; Jelinski, S.; Chuck, A.; Rowe, B.H.
Abstract : Introduction: Diabetes mellitus (DM) is a major chronic disease. Prevalence of diabetes was 9% globally in 2014 and 9.3% in Canada and 7.2% in Alberta in 2015. Complications of the disease are numerous and frequent. Hypoglycemia is one complication of diabetes treatment. The objective of this study was to quantify and characterize presentations by adults to Alberta emergency departments (EDs) for hypoglycemia associated with type 1 (T1DM) or type 2 (T2DM) diabetes.Methods: A retrospective cohort study was conducted using data for Alberta for a five-year period (fiscal years 2010/11-2014/15). Data were sourced from an administrative database: National Ambulatory Care Reporting System (NACRS). Records of interest were those with an ICD-10-CA diagnosis of DM-associated hypoglycemia (i.e., E10.63, E11.63, E13.63, or E14.63). A descriptive analysis was conducted.Results: Data extraction yielded 7, 835 presentations by 5, 884 patients. The majority of presentations were by males (56.2%) and median patient age was 62. These episodes constituted 0.08% of presentations to Alberta EDs and they occurred at an event rate of 0.67 episodes per 100 patient-years (95% CI: 0.66-0.69). The annual rate of presentations decreased by 11.8% during the five-year period. Most presentations (63.4%) involved transportation to the ED via ambulance. Relative to LOS for ED presentations for all reasons, average length-of-stay (LOS) was 3.2x longer and 1.4x longer for discharged and admitted patients, respectively. For 27.5% of presentations, an X-ray was obtained. Most hypoglycemic episodes (65.2%) were considered to be of moderate severity while 34.3% were considered to be severe. None were mild because all involved access to an ED. The condition mainly (absolute terms) afflicted people with T2DM and urban areas; however, it disproportionately afflicted people with T1DM and rural areas.Conclusion: For a condition that is largely preventable with effective blood glucose management, DM-associated hypoglycemia incurs significant healthcare resource use. People with DM would be better served with more effective and safer euglycemic agents.